2002
DOI: 10.1021/jf0115138
|View full text |Cite
|
Sign up to set email alerts
|

Biophenols in Table Olives

Abstract: Unprocessed olives are well-known sources of phenolic antioxidants with important biological properties. Processing methods to prepare table olives may cause a reduction of valuable phenols and may deprive the food of precious biological functions. The present work was undertaken to evaluate table olives produced in Greece as sources of biophenols. Commercially available olives were analyzed for their total phenol content by using the Folin-Ciocalteu reagent and for individual phenols by RP-HPLC. Samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
92
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 32 publications
14
92
0
3
Order By: Relevance
“…The results obtained for fresh olives are similar to those obtained for Portuguese cultivars (Pereira et al 2006), Tunisian cultivars (Ben Othman et al 2009), and Italian cultivars Piscopo et al (2014). However, processed olives contained higher amounts of phenolic compounds than those studied by Blekas et al (2002) and similar contents to those reported by Ben Othman et al (2009).…”
Section: Total Phenolic Contentsupporting
confidence: 83%
“…The results obtained for fresh olives are similar to those obtained for Portuguese cultivars (Pereira et al 2006), Tunisian cultivars (Ben Othman et al 2009), and Italian cultivars Piscopo et al (2014). However, processed olives contained higher amounts of phenolic compounds than those studied by Blekas et al (2002) and similar contents to those reported by Ben Othman et al (2009).…”
Section: Total Phenolic Contentsupporting
confidence: 83%
“…The health-promoting properties of the Mediterranean diet have been largely attributed to the antioxidant and free radical-scavenging activity of phenolic compounds contained in the dietary components. Table olives and olive oil are important components of the Mediterranean diet that provide numerous health benefits and are largely consumed all over the world (Blekas, Vassilakis, Harizanis, Tsimidou, & Boskou, 2002;Cioffi et al, 2010;Owen et al, 2004;Stark & Madar, 2002). In fact, many studies have reported that olive oil may have a role in the prevention of coronary heart disease and cognitive impairment (e.g., Alzheimer's disease) as well as it may have protective effects against cancers of the colon, breast, and ovary; diabetes accompanied by hypertriglyceridemia; and inflammatory and autoimmune diseases such as rheumatoid arthritis (Charoenprasert & Mitchell, 2012;Cicerale, Lucas, & Keast, 2010;Malheiro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning to the antioxidant activity, olive oil polyphenols revealed good properties (Gordon, PaivaMartins, & Almeida, 2001;Paiva-Martins, Gordon, & Gameiro, 2003) and olive leaves have been referred as a source of several antioxidants (Briante et al, 2002;Bouaziz & Sayadi, 2005;Meirinhos et al, 2005;Ranalli et al, 2006;Ferreira, Barros, Soares, Bastos, & Pereira, 2007). Also table olives have been studied in its polyphenol composition (Marsilio, Campestre, & Lanza, 2001;Blekas, Vassilakis, Harizanis, Tsimidou, & Boskou, 2002;Romero, Garcı´a, Brenes, Garcı´a, & Garrido, 2002;Romero et al, 2004;Pereira et al, 2006) and antioxidant activity (Owen et al, 2003;Boskou et al, 2006;Pereira et al, 2006). Nevertheless, as far as we know, it is the first time that a study on the antioxidant potential of stoned table olives ''alcaparras'' is reported.…”
Section: Introductionmentioning
confidence: 99%